Pemikiran Muhammad Iqbal Dalam Perspektif Filsafat Ketuhanan - Kirom, Syahrul (Aqlania, 2022)
This paper examines the divine philosophy of Muhammad Iqbal's thought. Iqbal tries to understand God by using ego. The ego is a representation of God. In the ego, religious experience is more important as an effort to get closer to God. This research method uses a descriptive-analytical approach. The study found that Muhammad Iqbal's understanding of God put more emphasis on an esoteric approach, not an exoteric approach. The conception of divine philosophy according to Muhammad Iqbal is actually how to function human potential, by always implementing Islamic teachings and the concept of monotheism. Thus, Muslims can practice monotheism in carrying out their worship.